Low cost and green synthesis of reduced graphene oxide-zeolitic imidazole framework 8 (rGO-ZIF8) using mother liquor recycling - Mohd Zaini, Muhammad Hailmi (2019)
Zeolitic imidazole frameworks-8 are have a high interest in industries application due to its properties which are high surface area, modifiable organic and high chemical and thermal stability. However, to synthesized ZIF-8 in large scale, there might be a problem on the cost because of the expensive imidazole species solvent. To this work, Green hybrid nanocomposite of reduced graphene oxide/zeolitic imidazolate framework-8 (rGO-ZIF-8) has been successfully fabricated via multi-recycling approach by re-using non-reactant reagents in supernatant known as mother liquor. This approach allowed minimal addition of fresh reactant and rGO was used as a template for in situ growth of ZIF-8. The solid product of each batch was collected and characterized by using XRD, TGA, FTIR, BET, FESEM and TEM. The non-reacted reagents in supernatant was then recovered and re-use for the subsequent cycle of synthesis up to 4 times. The XRD analysis shows that the ZIF-8 samples have diffraction peaks 2ϴ at 7.28, 10.35, 12.66, 14.64, 16.39, 17.97 peaks indicate that the formation of ZIF-8 was successful. The diffraction peaks for rGO-ZIF-8 shows the same pattern indicates that the addition of rGO does not changing the crystal structure of ZIF-8. The TGA results revealed that there was no significant difference in thermal stability of ZIF-8(Z1) and all the recycled ZIF-8 samples. For rGO-ZIF-8 samples, higher amount of rGO added was found to increase the thermal stability of the samples. The surface area and pore volume of the recycled ZIF-8 samples were lowered compared to ZIF-8(Z1). The surface area of 70r-Z and 140r-Z decrease proportionally with the addition high amount rGO suggests that there might be strong association between ZIF-8 and rGO that the cavities inside ZIF-8 might be partially blocked by rGO sheets. It was demonstrated that ZIF-8 nanoparticles anchored well on the surfaces of rGO and high product yield can be maintained. This approach allows low cost and green synthesis of rGO-ZIF-8 synthesis as the waste discarded is minimal